2022
DOI: 10.3389/fspor.2022.903937
|View full text |Cite
|
Sign up to set email alerts
|

A contemporary understanding of iron metabolism in active premenopausal females

Abstract: Iron metabolism research in the past decade has identified menstrual blood loss as a key contributor to the prevalence of iron deficiency in premenopausal females. The reproductive hormones estrogen and progesterone influence iron regulation and contribute to variations in iron parameters throughout the menstrual cycle. Despite the high prevalence of iron deficiency in premenopausal females, scant research has investigated female-specific causes and treatments for iron deficiency. In this review, we provide a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 132 publications
0
5
0
Order By: Relevance
“…The observed changes in ferritin levels may be indicative of the increasing intensity of the training program and of the modest increases in lean mass observed during the pre-season period, a pattern consistent with the changes seen in female combat trainees over a 16 week basic combat training program [32]. Ferritin, unlike serum iron and transferrin saturation, tends to remain stable throughout the menstrual cycle [33], suggesting its specific role in capturing specific changes due to training load.…”
Section: Discussionmentioning
confidence: 81%
“…The observed changes in ferritin levels may be indicative of the increasing intensity of the training program and of the modest increases in lean mass observed during the pre-season period, a pattern consistent with the changes seen in female combat trainees over a 16 week basic combat training program [32]. Ferritin, unlike serum iron and transferrin saturation, tends to remain stable throughout the menstrual cycle [33], suggesting its specific role in capturing specific changes due to training load.…”
Section: Discussionmentioning
confidence: 81%
“…The observed changes in ferritin levels may be indicative of the increasing intensity of the training program and of the modest increases in lean mass observed during the pre-season period, a pattern consistent with the changes seen in female combat trainees over a 16 week basic combat training program [ 33 ]. Ferritin, unlike serum iron and transferrin saturation, tends to remain stable throughout the menstrual cycle [ 34 ], suggesting its specific role in capturing specific changes due to training load.…”
Section: Discussionmentioning
confidence: 99%
“…Inference from research has suggested that prolonged use of OCP is a beneficial intervention for preventing iron depletion and the risk of iron deficiency as a result of the observed changes to menstrual bleeding (Alfaro‐Magallanes et al, 2022 ). Within athletic females, it is worth noting that iron status is consistently challenged through increases in iron loss through exercise‐associated mechanisms, inflammatory derived increases in hepcidin and subsequent alterations in iron regulation, increased risk of heavy menstrual bleeding, and low dietary iron intake from various dietary intake behaviors and patterns (e.g., vegan, vegetarian, macronutrient restrictive, and dietary restrictive; Badenhorst et al, 2022 ). The reduction in total iron lost through one of these mechanisms is likely to be considered beneficial for the sustainability of female athletic performance.…”
Section: Discussionmentioning
confidence: 99%